VD_FINDINFO ML / 2014 / 253 vom 30. Oktober 2014 - VD Tribunal cantonal (2014)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, TRANSACTION JUDICIAIRE, FORME ÉCRITE | 12 CO, 148 CPP-VD, 80 al. 2 ch. 1 LP, 81 al. 1 LP